A Review of Psoriasis, Therapies, and Suicide. Issue 4 (July 2016) - Gooderham, Melinda; Gavino-Velasco, Jennifer; Clifford, Cole; MacPherson, Alex; Krasnoshtein, Flora; Papp, Kim
Many chronic medical disorders are associated with psychiatric morbidity. Yet the psychological burden of these disorders often goes unnoticed. In dermatology, psoriasis has a higher association with psychiatric illness, including depression and suicide risk, compared with many other conditions. Studies suggest that effective treatment of psoriasis results in the improvement of psychiatric morbidity, particularly depression and anxiety. New biologic treatments for psoriasis may offer help beyond clearing of the skin in these patients and may lead to a reduction of psychiatric morbidity. Although concerns have been raised regarding the potential link between interleukin-17R blockade in the treatment of psoriasis and suicide, current literature provides no evidence to support this association.